S12 Unscheduled healthcare resource utilisation and health-related quality of life before and after omalizumab initiation in UK clinical practice: the apex study. (2nd December 2011) - Barnes, N; Radwan, A; Percival, F
Abstract : Objectives: The efficacy and safety of omalizumab for the treatment of severe persistent allergic asthma have been demonstrated in randomised controlled clinical trials. However, there are limited "real world" data on its effects on healthcare resource utilisation or health-related quality of life (QoL) in UK clinical practice. Methods: A 10 centre retrospective observational study (APEX) compared 12 months pre- vs 12 months post-omalizumab initiation in patients aged =12 years with severe persistent allergic asthma. All patients received =1 dose of omalizumab. Patients who had received omalizumab in a clinical trial were excluded. Hospital records were reviewed to obtain data on hospital resource use and routinely used QoL measures for example, Asthma Quality of Life Questionnaire (AQLQ) at baseline (pre-omalizumab), 16 weeks and up to 12 months following omalizumab initiation. Results: Mean in-patient hospital admissions fell by 61% from 1.30 to 0.51 (p<0.001) and mean in-patient bed days fell by 70% from 9.10 to 2.74 (p<0.001) per patient. In the subgroup of patients hospitalised for asthma in the 12 months pre-omalizumab (n=81), mean in-patient hospital admissions fell by 70% from 2.19 to 0.65 (p<0.001) and mean in-patient bed days fell by 74% from 14.86 to 3.83 (p<0.001) per patient. Similarly, mean Accident and Emergency department attendances fell by 70% from 1.52 per patient in the 12 months pre-omalizumab to 0.46 in the 12 months post-omalizumab (p<0.001). Other resource use, such as outpatient attendances (excluding visits made solely for omalizumab administration), nurse appointments and telephone consultations remained unchanged following omalizumab initiation. QoL data were not available for all patients at every time point. However, where data were available, mean AQLQ scores increased from 3.09 at baseline to 5.01 at 16 weeks (n=90) and to 5.22 at 12 months (n=29). Conclusions: Treatment with omalizumab is associated with a clinically and statistically significant reduction in unplanned hospital resource utilisation and improvements in patients' QoL.